The Socio-Cultural Context of Mawarannahr During the Period of Sufi Allayar - Tojiyev Fazliddin Khayitmurad (Scientific Trends, 2026)
This article examines the life and scholarly activity of Sufi Allayar, a prominent figure in seventeenth- and early eighteenth-century Central Asia, within the context of socio-political and cultural transformations in the region. It highlights the decline of Sufism, the weakening of spiritual and educational institutions, and the impact of internal wars, political fragmentation, and foreign invasions on the socio-economic and cultural development of Mawarannahr . Using comparative analysis of literary and historical sources including local chronicles, archival documents, memoirs, and philosophical works the study identifies key causes of spiritual and cultural decline, as well as the approaches of Naqshbandi spiritual leaders to address these challenges. The article also underscores the role of Sufi Allayar and his contemporaries in promoting religious and moral guidance, resisting foreign and erroneous ideologies, and striving to maintain social cohesion during a period of profound instability.
Keywords: Sufi Allayar; Central Asia; Mawarannahr; Naqshbandi order; Sufism; seventeenth–eighteenth centuries; spiritual decline; socio-political change; Turkestan; literary analysis.